Implementation of Solar-Powered IoT-Based Smart Fertigation System for Romaine Lettuce and Pakcoy - Annisa Lestari Simanjuntak; Renny Eka Putri; Fadli Hafizulhaq; Abdul Syafiq bin Abdull Sukor (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study implemented a solar-powered Internet of Things (IoT)-based smart fertigation system for hydroponic cultivation of romaine lettuce (Lactuca sativa var. longifolia) and pakcoy (Brassica rapa L.) using the Deep Flow Technique (DFT). The system integrated an ESP32 microcontroller, environmental sensors, and the Arduino IoT Cloud platform to enable real-time monitoring and automatic control of pH and nutrient concentration. During the 30-day cultivation period, the system maintained an average pH of 6.11, an average TDS concentration of 907.15 ppm, and an average water temperature of 29.22 °C, while the photovoltaic power system provided sufficient energy for continuous operation. Romaine lettuce reached average values of 15.76 leaves, 14.38 cm plant height, 13.25 cm leaf length, and 10.37 cm leaf width, whereas pakcoy achieved 19.39 leaves, 19.67 cm plant height, 12.31 cm leaf length, and 7.95 cm leaf width, with both crops outperforming the control treatment. The results demonstrate that the proposed system maintained stable growing conditions and supported continuous vegetative growth throughout the cultivation period. Therefore, the integration of IoT technology, automated fertigation, and solar photovoltaic energy provides an effective and sustainable solution for hydroponic vegetable production. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action